2007
DOI: 10.1007/s11267-006-9095-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends of Non-sea Salt Sulfate and Nitrate in Wet Deposition in Japan

Abstract: Temporal trends of non-sea salt (nss-) sulfate and nitrate were analyzed from nationwide precipitation chemistry measurements provided by the Ministry of the Environment (MOE) for the 1988-2002 fiscal years (April-March). The concentrations and deposition of nss-sulfate were found to be decreasing, and those of nitrate were stable or slightly increasing at most sites. These deposition trends were discussed from the viewpoint of emissions of SO 2 and NO X during the period of interest. Because monitoring techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…1) (Noguchi et al, 2007a;Tsunogai et al, 2010), we obtained δ 18 O = +79 ± 20 ‰, which correspond to the δ 18 O values for NO − 3 atm (Durka et al, 1994;Morin et al, 2009;Alexander et al, 2009;Tsunogai et al, 2010). These findings indicated that an increase in the export flux of NO (Fig.…”
Section: δ 18 O and δ 15 N Values Of Atmospheric Nitratesupporting
confidence: 78%
See 1 more Smart Citation
“…1) (Noguchi et al, 2007a;Tsunogai et al, 2010), we obtained δ 18 O = +79 ± 20 ‰, which correspond to the δ 18 O values for NO − 3 atm (Durka et al, 1994;Morin et al, 2009;Alexander et al, 2009;Tsunogai et al, 2010). These findings indicated that an increase in the export flux of NO (Fig.…”
Section: δ 18 O and δ 15 N Values Of Atmospheric Nitratesupporting
confidence: 78%
“…Nitrate aerosol, nitric acid, and nitrous acid were collected for every 3 weeks from the monitoring tower at a height of 30 m (Fig. 1) using the filter pack method (flow rate = 4 L min −1 ) and a PM2.5 impactor (Noguchi et al, 2007b). Nitrogen oxides (NO 2 and NO) were collected monthly (every 3 or 6 weeks) from a height of 1.5 m using an Ogawa passive sampler.…”
Section: Deposition Rate Of Atmospheric Nitratementioning
confidence: 99%
“…Thus, we can evaluate the background fraction of NO − 3 (atm) within the total NO − 3 eluted from the normally forested watersheds from the groundwater of the island, which finally appears on the surface as spring, lake and/or stream water in shore areas. In addition, a monitoring observatory of the Acid Deposition Monitoring Network in East Asia (EANET) was established on the island in 2000 to quantify the acid deposition rate in background areas of eastern Asia (EANET, 2008;Noguchi et al, 2007). The monitoring has shown that the island received 12.7 mmol m −2 a −1 of NO (EANET, 2008), which corresponds to a small total fixed-N deposition rate of 4.5 kg ha −1 a −1 .…”
Section: Site Descriptionmentioning
confidence: 99%
“…This value corresponds to the annual mean wet deposition of nss-SO 4 2-via rainfall, 21.0 meq m -2 , in the rural area of western Hokkaido (Noguchi et al, 2007). The total deposition amount of inorganic nitrogen compounds (i.e., NH 4 + + + +NO 3 -) in the fog water observation period was 37.8 meq m -2 (Table 4), which is also similar to the annual wet deposition amount of 28.8 meq m -2 y -1 in the same area of western Hokkaido (Hayashi et al, 2006).…”
Section: Estimation Of Fog Water and Inorganic Ion Depositionmentioning
confidence: 92%